Respuesta :

Answer:

[tex]f(x)=\frac{x}{x+20} , g(x)=\frac{20x}{x-1}[/tex]

Step-by-step explanation:

we know that

To find the inverse of a function, exchange variables x for y and y for x. Then clear the y-variable to get the inverse function.

we will proceed to verify each case to determine the solution of the problem

case A) [tex]f(x)=\frac{x+1}{6} , g(x)=6x-1[/tex]

Find the inverse of f(x)

Let

y=f(x)

Exchange variables x for y and y for x

[tex]x=\frac{y+1}{6}[/tex]

Isolate the variable y

[tex]6x=y+1[/tex]

[tex]y=6x-1[/tex]

Let

[tex]f^{-1}(x)=y[/tex]

[tex]f^{-1}(x)=6x-1[/tex]

therefore

f(x) and g(x) are inverse functions

case B) [tex]f(x)=\frac{x-4}{19} , g(x)=19x+4[/tex]

Find the inverse of f(x)

Let

y=f(x)

Exchange variables x for y and y for x

[tex]x=\frac{y-4}{19}[/tex]

Isolate the variable y

[tex]19x=y-4[/tex]

[tex]y=19x+4[/tex]

Let

[tex]f^{-1}(x)=y[/tex]

[tex]f^{-1}(x)=19x+4[/tex]

therefore

f(x) and g(x) are inverse functions

case C) [tex]f(x)=x^{5}, g(x)=\sqrt[5]{x}[/tex]

Find the inverse of f(x)

Let

y=f(x)

Exchange variables x for y and y for x

[tex]x=y^{5}[/tex]

Isolate the variable y

fifth root both members

[tex]y=\sqrt[5]{x}[/tex]

Let

[tex]f^{-1}(x)=y[/tex]

[tex]f^{-1}(x)=\sqrt[5]{x}[/tex]

therefore

f(x) and g(x) are inverse functions

case D) [tex]f(x)=\frac{x}{x+20} , g(x)=\frac{20x}{x-1}[/tex]

Find the inverse of f(x)

Let

y=f(x)

Exchange variables x for y and y for x

[tex]x=\frac{y}{y+20}[/tex]

Isolate the variable y

[tex]x(y+20)=y[/tex]

[tex]xy+20x=y[/tex]

[tex]y-xy=20x[/tex]

[tex]y(1-x)=20x[/tex]

[tex]y=20x/(1-x)[/tex]

Let

[tex]f^{-1}(x)=y[/tex]

[tex]f^{-1}(x)=20x/(1-x)[/tex]

[tex]\frac{20x}{1-x}\neq \frac{20x}{x-1}[/tex]

therefore

f(x) and g(x) is not a pair of inverse functions